Analisis Getaran Kendaraan Sistem Satu Roda dalam tinjauan Dua Derajat Kebebasan - Pipit Wahyu Nugroho (Polinema Press, Politeknik Negeri Malang, 2019)
The comfort of the vehicle passenger of the vehicle and its stability are the important variables that are always needed by everyone who uses transportation. In order to achieve this goal, the suspension of the vehicle will play an important role because its function is to isolate passengers from the effects of excitation from outside the vehicle and also to control the wheels attached to the road surface. Therefore in this study, the influence of various types of suspensions on vehicle vibrations is observed in terms of comfort and stability. The type of suspension in this study is related to the level of suspensión stiffness namely the spring and the damper. Vehicle modeling to be applied in a one-wheeled vehicle with two degrees of freedom. The experimental study is conducted by loading of vehicle body weight and passengers to three type of suspension, soft, medium and hard. Vibration responses to be analyzed on the vehicle equation using Matlab to obtain the acceleration response of the displacement and the defelction. This research obtains a vibration response graph for each type of suspension for some kind of road profile.